On heavy machines dynamical loading under adjacent links shocks - Трубачев, Сергей Иванович; Лысюк, Дмитрий Степанович; Талимонова, Ольга Юрьевна (Eastern-European Journal of Enterprise Technologies, 2014)
The mathematical model, describing the dynamics under collision of heavy machinery adjacent links in the presence of gaps and other elements with a dead or smoothness zone of transfer functions of kinematic chains, is given. The model is designed using a procedure of "smoothing" discontinuous functions and regarding a variable structure. The specific example of a dynamic system and its numerical calculation is considered. The pressure between the roller and a workpiece is expressed by means of the Hertz’s law. The roller motion is represented as a plane-parallel motion. Four differential equations describe the process of the roller colliding against the workpiece. By using a numerical integration of differential equations, the solution in the form of diagrams is worked out. The developed technique will allow calculating the resource of the rolling mill table more precisely when designing and thereby, improving its technical level.